1997
DOI: 10.1295/polymj.29.713
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Rising Elution Fractionation of Polypropylenes Produced by Heterogeneous Ziegler-Natta Catalysts Containing Different Internal Donors

Abstract: ABSTRACT:Ethyl benzoate (EB), bis(2-ethyl hexyl) sebacate (BEHS), di-n-butyl phthalate (DNBP), and bis(2-ethyl hexyl) phthalate (BEHP) were employed as internal electron donors of heterogeneous Ziegler-Natta catalysts and the obtained polypropylene (PP) samples were fractionated by temperature rising elution fractionation (TREF). The influence of different internal donors on the tacticity distributions of PPs was compared. PPs have narrower tacticity distributions with aromatic esters. Based on TREF results, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Modified Busico Three-State Statistical Model. The defected pentads and heptads observed by 13 C NMR for the ZN-iPP fractions and the parent ZN-iPP are listed in [7][8][9][10][11][22][23][24][25][26] we notice a nonnegligible concentration of purely syndiotactic sequences (rrrrrr) in all the ZN fractions, including the fraction with the highest molar mass. In addition, stereoerrors of the type, rmrrrm or rmrrrr are also not detected.…”
Section: Molecular Fractions From Metallocene Ipp and Z-n Ipp: Fractimentioning
confidence: 97%
See 1 more Smart Citation
“…Modified Busico Three-State Statistical Model. The defected pentads and heptads observed by 13 C NMR for the ZN-iPP fractions and the parent ZN-iPP are listed in [7][8][9][10][11][22][23][24][25][26] we notice a nonnegligible concentration of purely syndiotactic sequences (rrrrrr) in all the ZN fractions, including the fraction with the highest molar mass. In addition, stereoerrors of the type, rmrrrm or rmrrrr are also not detected.…”
Section: Molecular Fractions From Metallocene Ipp and Z-n Ipp: Fractimentioning
confidence: 97%
“…[11][12][13][14][22][23] TREF 14,22 and solvent gradient extraction [11][12][13] led to fractions of increasing isotacticity and increasing molar mass, a result that clearly indicated a nonuniform interchain composition of defects. They also observed that most of the fractions contained syndiotactic rrrr pentads and, as in other works, [7][8][9][10][11][12][13][24][25][26] it was proposed that some of the propagation errors were "blocky" in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] This technique reveals even minor differences in stereoregularities of polymers prepared with similar catalysts. [9,10,[18][19][20] Earlier Tref analysis of the ''isotactic'' fractions of poly(propylene) (the fractions insoluble in o-xylene at 95 8C) prepared with several catalysts of the type TiCl 4 / MgCl 2 /internal electron donor has shown that these fracions differ quite substantially in stereoregularity depending on the type of the internal donor as well as the type of the external electron donor, which is used in combination with AlEt 3 as a part of a cocatalyst mixture. [9,10] This paper describes in detail the quantitative aspects of the distribution of isospecific centers in these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Fractionation by TREF of polypropylene followed by GPC and NMR analysis has been described by Mingozzi 98 and Xu et al 100,101 Preparative fractionation by TREF of propylene copolymers have been reported by Usami, 94 Kakugo et al, 96 Abiru et al 102 and Feng et al 103 …”
Section: Polypropylene Analysismentioning
confidence: 97%